Penyelesaian Kerugian Negara Yang Disebabkan Tindak Pidana Korupsi Dalam Pengelolaan Keuangan Negara Di Badan Usaha Milik Negara PT. ASABRI (Persero) - Saputro, Bayu (UI Scholars Hub, 2024)
This article aims to examine the settlement of state losses caused by criminal acts of corruption in the management of state finances at the State-Owned Enterprise PT. Asabri (Persero). The research results show that the financial status of BUMN PT. Asabri is state finance, so when a criminal act of corruption occurs, a mechanism is needed to resolve state losses. Criminal law enforcement has been carried out as well as a mechanism for paying compensation to the state to resolve state losses. However, it seems that the settlement of state losses by convicts through the payment of compensation money to the state is not enough to replace the entire value of state losses caused by criminal acts of corruption. Obstacles to resolving state losses are contained in the provisions of Article 18 paragraph (1) letter b of the Corruption Eradication Law. This article stipulates that the payment of replacement money is limited to the value of the property obtained by the perpetrator of the criminal act of corruption. This limitation means that convicts are only responsible for returning the value of losses to the state they obtained unlawfully. In addition, state losses at PT. Asabri is not part of the convict's responsibility. As we know, criminal acts of corruption are very likely to cause other losses that arise outside of the property obtained by the perpetrator by violating the law.